Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/jbm.a.35507
|View full text |Cite
|
Sign up to set email alerts
|

Culture of hESC‐derived pancreatic progenitors in alginate‐based scaffolds

Abstract: The effect of alginate-based scaffolds with added basement membrane proteins on the in vitro development of hESC-derived pancreatic progenitors was investigated. Cell clusters were encapsulated in scaffolds containing the basement membrane proteins collagen IV, laminin, fibronectin, or extracellular matrix-derived peptides, and maintained in culture for up to 46 days. The cells remained viable throughout the experiment with no signs of central necrosis.Whereas non-encapsulated cells aggregated into larger clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 61 publications
2
21
1
Order By: Relevance
“…The number of bihormonal cells was not significantly affected by encapsulation ( Figure 1c). Interestingly, the cells encapsulated during the entire period of differentiation (S7 bead[S0-S7] ) displayed a significant increase of the glucagon-and somatostatin-expressing cell populations, but not insulin, as previously reported 29 .…”
Section: Encapsulation Promotes the Expression Of Islet Hormones And supporting
confidence: 79%
See 2 more Smart Citations
“…The number of bihormonal cells was not significantly affected by encapsulation ( Figure 1c). Interestingly, the cells encapsulated during the entire period of differentiation (S7 bead[S0-S7] ) displayed a significant increase of the glucagon-and somatostatin-expressing cell populations, but not insulin, as previously reported 29 .…”
Section: Encapsulation Promotes the Expression Of Islet Hormones And supporting
confidence: 79%
“…In order to eliminate any interference from a possible aggregation/cell clustering effect, we focused on the encapsulation of single cells. This is in contrast with previous studies, which deliberately used clusters to assess the alginate encapsulation effect 29 . We showed here for the first time that The general impact of the 3D organization for the cell differentiation potential is also supported by the introduction of air liquid interface 1 or suspension culture 46 Our subsequent proteome analyses suggested that encapsulation strongly boosts β -cell fate in a stage-specific manner, by promoting early-stage differentiation and potentiating the islet signature during the later stages.…”
Section: Pathway Analysis Is Suggestive Of Encapsulation Regulating Tmentioning
confidence: 74%
See 1 more Smart Citation
“…A positive effect of encapsulation has been shown for the development of neonatal porcine islets into mature islets upon culture in serum-containing media [56]. This may be partly due to the hindering of aggregation of clusters upon culture, as has also been shown for human pancreatic progenitors when cultured in alginate beads [57]. hESC have been differentiated to definitive endoderm in alginate capsules [58].…”
Section: The Inner Life Of the Capsule-oxygen Supply And Microenvironmentioning
confidence: 98%
“…hESC have been differentiated to definitive endoderm in alginate capsules [58]. For pancreatic progenitors, no effect on differentiation was seen when extracellular matrix (ECM) components (proteins and peptides) were added to the capsule composition [57]. Although no effect was seen in the previous study, the design of the capsule microenvironment to mimic the natural microenvironment has drawn recent attention [59]and positive effects have been shown on beta cell lines [60] as well as on human islets [61].…”
Section: The Inner Life Of the Capsule-oxygen Supply And Microenvironmentioning
confidence: 99%